Scleral crosslinking using genipin can compromise retinal structure and function in tree shrews. (June 2022) - Hamdaoui, Mustapha El; Levy, Alexander M.; Stuber, Aaron B.; Girkin, Christopher A.; Kraft, Timothy W.; Samuels, Brian C.; Grytz, Rafael
Abstract: Scleral crosslinking using genipin has been identified as a promising treatment approach for myopia control. The efficacy of genipin to alter biomechanical properties of the sclera has been shown in several animal models of myopia but its safety profile remains unclear. In this safety study, we aim to investigate the effect of scleral crosslinking using retrobulbar injections of genipin on retinal structure and function at genipin doses that were shown to be effective in slowing myopia progression in juvenile tree shrews. To this end, three or five retrobulbar injections of genipin at 0 mM (sham), 10 mM, or 20 mM were performed in one eye every other day. Form deprivation myopia was induced in the injected eye. We evaluated retinal function using full-field electroretinography and retinal structure using in vivo optical coherence tomography imaging and ex vivo histology. The optical coherence tomography results revealed significant thinning of the peripapillary retinal nerve fiber layer in all genipin treated groups including the lowest dose group, which showed no significant treatment effect in slowing myopia progression. In contrast, inducing form deprivation myopia alone and in combination with sham injections caused no obvious thinning of the retinal nerve fiber layer. Electroretinography results showed a significant desensitizing shift of the b-wave semi-saturation constant in the sham group and the second highest genipin dose group, and a significant reduction in b-wave maxima in the two highest genipin dose groups. The ex vivo histology revealed noticeable degeneration of photoreceptors and retinal pigment epithelium in one of two investigated eyes of the highest genipin dose group. While scleral crosslinking using genipin may still be a feasible treatment option for myopia control, our results suggest that repeated retrobulbar injections of genipin at 10 mM or higher are not safe in tree shrews. An adequate and sustained delivery strategy of genipin at lower concentrations will be needed to achieve a safe and effective scleral crosslinking treatment for myopia control in tree shrews. Caution should be taken if the proposed treatment approach is translated to humans. Highlights: Repeated retrobulbar injections of genipin at 10 mM or higher compromise retinal structure and function in tree shrews. Scleral crosslinking using genipin at doses that are effective in slowing myopia are not safe in tree shrews. Caution should be taken if scleral crosslinking using genipin is translated to humans.